The place of the handphone in teenagers' lives : understanding Singapore youth mobile culture by examining teenagers' use of the handphone for communication and co-ordination among peers. - Ho, Elaine Ming Sim. (2008)
This study is an exploratory effort in exploring the phenomenon of handphone usage and its implications for daily life.